2017
DOI: 10.5812/mejrh.57480
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Stresses and Musculoskeletal Disorders Among Nurses: A Cross-Sectional Study

Abstract: Objectives: Work-related musculoskeletal disorders are a significant occupational problem among employees and workers. This study attempted to explore the effect of stressors in the hospital environment on nurses' development of musculoskeletal disorders. Methods: We conducted a cross-sectional survey in a random sample of 123 hospital nurses from Semnan University of Medical Sciences. Data were collected during working days over 3 months starting from January 2014. Participants completed a standardized questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
2
11
0
2
Order By: Relevance
“…The shoulder, elbow joint, wrist, knee joint, hip joint, and ankle joint were further divided into the left and right side. Numerous studies have indicated that shoulder, neck, and lower back discomfort are health problems commonly seen in nurses [3,11,16,32,33] The results of the present study indicated that the body locations where discomfort was most commonly felt among participants was, in descending order, the right shoulder, left shoulder, neck, and lower back, with prevalence rates of 85.8%, 80.9%, 62.4%, and 60.4%, respectively. This result is similar to those of many other studies.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The shoulder, elbow joint, wrist, knee joint, hip joint, and ankle joint were further divided into the left and right side. Numerous studies have indicated that shoulder, neck, and lower back discomfort are health problems commonly seen in nurses [3,11,16,32,33] The results of the present study indicated that the body locations where discomfort was most commonly felt among participants was, in descending order, the right shoulder, left shoulder, neck, and lower back, with prevalence rates of 85.8%, 80.9%, 62.4%, and 60.4%, respectively. This result is similar to those of many other studies.…”
Section: Discussionmentioning
confidence: 52%
“…Musculoskeletal disorder (MSD) is defined as connective tissue or musculoskeletal disease that causes muscle pain or injury due to sudden or continuous contact, repeated exercise, force, vibration, or incorrect posture movements [1,2]. MSD has been recognized as one of the most common occupational injuries, and nurses in the medical service industry have been identified as a high-risk group for such injuries [3]. The worldwide epidemiological studies have revealed a high incidence and prevalence of low back musculoskeletal complaints among nurses [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main causes of musculoskeletal diseases involve lifting heavy items, working in awkward postures, and performing similar tasks repetitively 37 . These ergonomic risk factors have been reported to be the most important factors contributing to the incidence of musculoskeletal diseases; however, psychosocial factors have also been emphasized recently [38][39][40] . Rheumatoid arthritis (RA), a subgroup of musculoskeletal system diseases and the most common autoimmune disease 41 , has been associated with a family history of RA and psychological stresses such as depression and anxiety 42,43 .…”
Section: Discussionmentioning
confidence: 99%